Rodentisida Nabati Singkong Mentah (Manihot esculenta) sebagai Alternatif Pengendalian Hama Tikus - Viony, Manasye; Rosdiana, Laily; Roqobih, Fikky (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
Rats are nuisance animals that can damage the economy and bring diseases to humans. To control rat populations, rodenticides are often used that contain toxic chemicals that are not environmentally friendly. However, there is an alternative to reducing the use of rodenticides, namely using vegetable rodenticides made from natural ingredients such as cassava which contains cyanide acid. Cyanide acid is very dangerous and can cause illness and even death if ingested. This research is a literature review. Research conducted by Fazriyawati and Rahmawati used 50 male white mice of Mus musculus species as samples. Samples were treated with cassava rodenticide doses of 40 grams, 60 grams, 80 grams, and 100 grams. The results showed that the highest mice mortality occurred at a dose of 100 grams with an average bait consumption of 62.48 grams and a mice mortality percentage of 60%. Thus, the conclusion of this study is that raw cassava has the potential as an effective vegetable rodenticide. Keywords: Mice, Plant-based Rodenticide, Raw Cassava